Remains of Mosses and Freshwater Animals in some Holocene Lake and Bog Sediments from Greenland. - Fredskild, Bent; Jacobsen, Niels; Røen, Ulrik (Meddelelser om Grønland, 1975)
Core samples of South Greenland lake sediments have been investigated as regards macroscopical remains of mosses and freshwater animals. Besides many widespread species the deeper samples contained species now occurring only in North Greenland, e.g. Bryum neodamense ssp. ovatum and Lepidurus arcticus. During the hypsithermal, Cristatella mucedo lived in one of the lakes. The upper samples are poor in species, partly a result of an oligotrophication of the lakes. From Peary Land, North Greenland, remains from one lake and one bog have been determined. The species found all occur in present day Peary Land.